Surface refractive index sensor based on titanium dioxide composite thin film for detection of cadmium ions - Sheh Omar, Nur Alia; Irmawati, Ramli; Fen, Yap Wing; Muhamad, Ernee Noryana; Kamal Eddin, Faten Bashar; Anas, Nur Ain Asyiqin; Md Ramdzan, Nur Syahira; Muhamad Fauzi, Nurul Illya; Mahdi, Mohd Adzir (Elsevier, 2022)
In this work, a refractive index sensor using TiO2 extracted from moringa leaves-based nanocomposite thin film was developed to detect cadmium ions in an aqueous solution. The experimental results showed a good sensitivity response of 0.4825° ppm−1, a strong binding affinity of 1.4362 ppm−1, and a low signal-to-noise ratio of 0.0755. The proposed sensor also showed good selectivity towards cadmium ions compared to zinc and mercury ions. The changes in the optical properties of titanium dioxide-based nanocomposite thin film towards different concentrations of cadmium ions solution were further demonstrated theoretically. Also, the observed increase in the surface roughness using atomic force microscopy proved the binding of Cd ions to the sensor film. This study is proposing a new potential of titanium dioxide extracted from moringa leaves-based nanocomposite thin film as a surface refractive index sensor for the detection of cadmium ions.